Motivational Correlates, Satisfaction with Life, and Physical Activity in Older Adults: A Structural Equation Analysis - Rodrigues, Filipe (2023)
Background: Motivation is a crucial factor in predicting health-related outcomes, and understanding the determinants of motivation can provide valuable insights into how to improve health behaviors and outcomes in older adults. In this study, we aimed to investigate the associations between intrinsic and extrinsic exercise motivation, basic psychological needs, satisfaction with life, and physical activity among the elderly population. Methods: The sample consisted of 268 older adults (59 male, 209 female) aged 65–90 years old (Mage = 68.11, SD = 6.95). All participants reported that they were exercising, on average, 1.65 days (SD = 0.51) per week. Factor analysis was conducted using a two-step approach. First, a confirmatory factor analysis and then a structural equation model considering all variables under analysis was performed. Results: the structural model displayed acceptable fit to the data: χ2/df = 3.093; CFI = 0.913; TLI = 0.908; SRMR = 0.071; RMSEA 0.079 [0.066, 0.092]. Significant direct effects were found as theoretically proposed, namely: (a) intrinsic motivation were positively and significantly associated with basic psychological need satisfaction (p < 0.001); (b) extrinsic motivation were negatively but not significantly associated with basic psychological needs (p < 0.001); and (c) basic psychological need satisfaction were positively and significantly associated with satisfaction with life (p < 0.001) and physical activity (p < 0.001). Conclusions: Intrinsic motivation and basic psychological needs play a crucial role in shaping exercise behavior and overall well-being. By understanding these motivation and needs, exercise and health professionals can work towards fulfilling them and achieving a greater sense of satisfaction in the life of the elderly and promote exercise adherence.